FRI0570 At Pre-Clinical Stage; Connective Tissue Disease is Indistinguishable from Other Inflammatory Arthritis on Ultrasound in Ccp-Negative Early Arthritis Patients. (9th June 2015) - Zayat, A.S.; Aleyan, A.; Hensor, E.M.; Emery, P.; Vital, E.M.
Abstract : Background: ANA positivity is a common finding in patients presenting with inflammatory joints symptoms without connective tissue disease (CTD) features. These patients can be seropositive (i.e. CCP and RF) or sero-negative. A group of these patients may not have enough findings to meet the RA classification criteria. There are limited data on long-term prognosis (i.e. disease progression) on this subgroup of patients. Objectives: To assess if musculoskeletal ultrasound (US) can predict future diagnosis of CTD in ANA-positive CCP negative arthralgia. Methods: Patients with new inflammatory joint symptoms presented to early arthritis clinic where recruited into Inflammatory Arthritis Continuum (IACON) study. These patients neither satisfied OA nor CTD diagnosis at presentation. Patients had a baseline clinical and imaging assessment and were followed up over 1-4 years for determination of ultimate diagnosis at endpoint. US imaging of hands, wrists, elbows, knees, feet and ankle was performed. Synovitis and erosions were assessed using OMERACT definitions and scoring. The analysis focused on ANA positive patients. To compare baseline US between endpoint diagnosis groups, Kruskal-Wallis tests were used. Results: A total of 151 ANA positive patients were recruited; 73 (48.3%) were CCP negative, of whom 17 (23%) satisfied the RA classification criteria at presentation, 45 (61%) were diagnosed as undifferentiated inflammatory arthritis (UA) and 11 (15%) had other diagnoses. Of the 45 UA patients, after 1-4 years of follow up, 10 (22%) were ultimately diagnosed as CTD (4 SLE, 2 systemic sclerosis, 3 primary Sjogren's syndrome and one undifferentiated CTD). The remaining 35 satisfied other diagnostic criteria or remained undifferentiated. After 12 months, 9/10 patients with an endpoint diagnosis of CTD had persistent ANA positivity compared to 13.4% of the other patients. In those with UA at baseline, 33.3% of endpoint CTD patients had ultrasound synovitis (GS ≥2 and/or PD≥1) at baseline in comparison to 45% of endpoint inflammatory arthritis (IA), 50% of endpoint UA and 44% of other non-inflammatory diagnoses. GS and PD scores at baseline did not differ between endpoint diagnoses (Table 1 ). Conclusions: In absence of CCP, patients with ANA-positive early onset inflammatory arthritis that were ultimately diagnosed as a CTD were clinically and sonographically indistinguishable from those were ultimately diagnosed as seronegative RA or SpA. Although PD appears to be present in third of CTDs in the early pre-diagnosis phases, this cannot in its own predict the CTD development. Similarly, presence of PD synovitis did not mean development of specific IA such as RA. Disclosure of Interest: None declared